(untitled) (Journal of Economic Research & Business Administration, 2015)
In our country efficiency of use of monetary resources is defined by elements of profitability and turns of assets. Acceleration of the movement of current assets doesn’t demand heavy expenses, and also to lead to a uvilecheniye of outputs. But inflation will quickly depreciate current assets. The enterprise trogit these funds for purchase of materials and fuel and energy resources. Not stability of buyers holds the main part of money. Communications with it are shown in this article western practical models and ways use of systems of planning of resources. In domestic practice advise to use these models at strong inflations.